Managing Agricultural Weather Risks in the State of Santa Catarina, Brazil - Arias Carballo, Diego (World Bank, Washington, DC, 2015)
Agriculture plays an important role in the state of Santa Catarina, Brazil. Most of its production depends on small family-owned farms, which are greatly exposed to climatic and price shocks. In order to help small farmers to manage risks, the federal and state governments have been carrying out several programs and measures to reduce and transfer agricultural risks. Santa Catarina ranks seventh out of 26 Brazilian states in terms of agricultural production. The states most important perennial crops are corn, soybean, tobacco, rice, beans, onions, and wheat. About 20 percent of the population lives in rural areas, of which some 90 percent are farmers. The most prominent climatic challenges are floods in the coastal region and droughts in the western plateau. Of these extreme weather events, floods are the most visible, because they receive widespread media coverage and sometimes cause deaths. However, drought poses a much more significant challenge to agricultural productivity. Given that most farms in Santa Catarina are small and that agricultural production is mainly rain fed, weather risks play a key role in the production variability and farmers income. In addition to government-funded preventive measures, farmers take other actions to protect themselves from weather risks. One traditional method is the diversification of income. Farmers in Santa Catarina often cultivate several crops with different growth and harvest cycles. When drought does occur it may damage some crops but it is unlikely to last long enough to affect all crops. Moreover, many farmers also farm animals, especially cows, pigs, chickens, and turkeys as a savings mechanism against the whims of the weather.